Yams botany, production and uses - Thompson, Anthony Keith (Agriculture) (Botany, production and uses., 2021)
"Dioscorea species, commonly known as yam, are tuberous plants which constitute a major staple food in many parts of Africa, Southeast Asia and the South Pacific. This book covers botany, taxonomy, composition and uses, cultivation, production, disessea and pests, and storage"--